A NEEDS ASSESSMENT APPROACH TO ENGLISH FOR SPECIFIC PURPOSES (ESP) BASED SYLLABUS DESIGN IN BANGLADESH VOCATIONAL AND TECHNICAL EDUCATION (BVTE) - Rauf, Md Abdur (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
This paper describes the initial phase of a needs analysis which is developed in the context of Bangladesh Vocational and Technical Education (BVTE) with the aim to identify the needs of a target group of learners and introduce English for Specific Purposes (ESP) course design. Although the compulsory English for Academic Purposes (EAP) courses have been used at various programs of BVTE since 1996, they were not based on any systemic Needs Analysis nor have they been subjected to any evaluation. The paper also aims to conducts a Needs Analysis to obtain data which will be used to develop a meaningful, useful and beneficial, common core ESP programme for Bangladesh Vocational and Technical Board (BVTB) students. This process takes into account the needs of the various stakeholders involved including the policy makers, decision-makers, subject and language teachers and prospective employers. It mainly will make use of Hutchinson and Waters’ (1987) Learning-centred approach, Holliday and Nunan’s (1988) Needs Analysis description for conducting the Needs Analysis and specifying the content for a common-core ESP course. A mix method is adopted with questionnaires, semi-structured interviews, classroom observation and document study being the main data gathering tools, in order to ensure triangulation of data.